Developing Ethnomathematics-Based Learning Media on Fractions - Ayu, Karmila; Azmidar, Azmidar (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
Using ethnomathematics method, this study attempts to create and assess the quality of learning materials about fractions, especially equivalent fractions, related to local culture. The five steps of ADDIE development modelanalysis, design, development, implementation, and evaluation—are used in this study along with Research and Development (R&D) techniques. As a contextual method for learning equivalent fractions, fraction board media representing the shape of traditional Bugis cakes katirisala (rectangle), sikaporo (hexagon), and cucuru' bayao (circle) are created. With a percentage of 83.33% from material experts and 96.66% from media experts, the results of expert validation indicate that the developed media has a high level of validity and is included in the "very valid" category. Meanwhile, the results of the practicality test from the teacher and student surveys indicate that this media is useful, with a practical category of 79.76% from students and a very practical category of 100% from teachers. Regarding efficacy, the N-Gain value of 0.88 indicates that student learning outcomes have increased to the "high" category, indicating that this media has succeeded in helping students understand the concept of fractions. Based on the information obtained, it can be said that the fraction board teaching material made using ethnomathematics has met the requirements of validity, usability, and efficacy and is suitable for use in the elementary school mathematics curriculum.